Bifidobacterium canis sp. nov., a novel member of the Bifidobacterium pseudolongum phylogenetic group isolated from faeces of a dog (Canis lupus f. familiaris) - Neuzil-Bunesova, Vera; Lugli, Gabriele Andrea; Modrackova, Nikol; Makovská, Marie; Mrazek, Jakub; Mekadim, Chahrazed; Musilova, Sarka; Svobodova, Ivona; Spanek, Roman; Ventura, Marco; Killer, Jiri (International journal of systematic and evolutionary microbiology, 2020)
A fructose-6-phosphate phosphoketolase-positive strain (GSD1FST) was isolated from a faecal sample of a 3 weeks old German Shepherd dog. The closest related taxa to isolate GSD1FST based on results from the EZBioCloud database were Bifidobacterium animalis subsp. animalis ATCC 25527T, Bifidobacterium animalis subsp. lactis DSM 10140T and Bifidobacterium anseris LMG 30189T, belonging to the Bifidobacterium pseudolongum phylogenetic group. The resulting 16S rRNA gene identities (compared length of 1454 nucleotides) towards these taxa were 97.30, 97.23 and 97.09 %, respectively. The pairwise similarities of strain GSD1FST using argS, atpA, fusA, hsp60, pyrG, rpsC, thrS and xfp gene fragments to all valid representatives of the B. pseudolongum phylogenetic group were in the concatenated range of 83.08-88.34 %. Phylogenomic analysis based on whole-genome methods such as average nucleotide identity revealed that bifidobacterial strain GSD1FST exhibits close phylogenetic relatedness (88.17 %) to Bifidobacetrium cuniculi LMG 10738T. Genotypic characteristics and phylogenetic analyses based on nine molecular markers, as well as genomic and comparative phenotypic analyses, clearly proved that the evaluated strain should be considered as representing a novel species within the B. pseudolongum phylogenetic group named as Bifidobacterium canis sp. nov. (GSD1FST=DSM 105923T=LMG 30345T=CCM 8806T).
Keywords: zastoupení bazí; RNA ribozomální 16S; Bacterial Typing Techniques; bakteriální geny; DNA bakterií; Feces; psi; Bifidobacterium; Genes, Bacterial; RNA, Ribosomal, 16S; techniky typizace bakterií; fylogeneze; DNA, Bacterial; Aldehyde-Lyases; feces; Sequence Analysis, DNA; sekvenční analýza DNA; zvířata; Base Composition; Dogs; Animals; Phylogeny; aldehydlyasy